2022
DOI: 10.1080/19490976.2022.2156764
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous antibiotic resistance gene contributes to intestinal inflammation by modulating the gut microbiome and inflammatory cytokine responses in mouse

Abstract: Dysregulation of the gut microbiota by environmental factors is associated with a variety of autoimmune and immune-mediated diseases. In addition, naturally-occurring extracellular antibiotic resistance genes (eARGs) might directly enter the gut via the food chain. However, following gut microbiota exposure to eARGs, the ecological processes shaping the microbiota community assembly, as well as the interplay between the microbiota composition, metabolic function, and the immune responses, are not well understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 96 publications
1
2
0
Order By: Relevance
“…Oppositely other evidence, in line with our results, found a positive correlation between Alistipes and arachidonic acid [43]. However, the same study focused on extracellular antibiotic resistance genes, defined…”
Section: Discussionsupporting
confidence: 91%
“…Oppositely other evidence, in line with our results, found a positive correlation between Alistipes and arachidonic acid [43]. However, the same study focused on extracellular antibiotic resistance genes, defined…”
Section: Discussionsupporting
confidence: 91%
“…Metabolic stress leads to inflammation, and inflammation itself will destroy the metabolic balance of the body. Therefore, metabolic disorder and inflammatory reaction may form a vicious circle ( 32 ). Therefore, these results indicated that IFN-τ participated in these metabolic pathways to interfere with the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…For the ARGs in rivers could enter the body by drinking water (Zhang, Qin, et al, 2021), it is indicated that the ARGs in the rivers with nature reserves of wild animals could be moved to wild animals by drinking. The gut microbiota plays a vital role in the health of wild animals by providing essential nutritional services and protection against the invasion of intestinal pathogens (Fackelmann et al, 2021), and regulating multiple aspects of microbial metabolite pools that could affect the gut barrier and the polarization of immune cells (Tan et al, 2023). Many studies have shown that ARGs can be transferred into the gut microbiota (Khan et al, 2020;Lamberte & van Schaik, 2022;Rolain, 2013), if the ARGs entry into the gut will have a significant impact on the gut microbiota, which may lead to various diseases and represent unknown risks to wild animals (Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%